Mirrors for Princes: Both Sides of the Tongue - Slavs and Tatars (NYUAD Gallery; JRP | Ringier, 2015)
Exhibition catalog. Feb-May 2015. Texts: Maya Allison, Anthony Downey, Beatrix Ruf, Neguin Yavari, Manan Ahmed Asif, Anna Della Subin, Lloyd Ridgeon, David Crowley.
English; Arabic
Keywords: Cultural Exchange (3GdJHGOd(B_(3GdKbGaj s; N4390-5098 Visual Arts- Exhibitions; Political writing